Epidemiological and Molecular Characteristics of the PB1-F2 Proteins in H7N9 Influenza Viruses, Jiangsu. (20th January 2015) - Wei, Pingmin; Li, Wei; Zi, Hairong; Cunningham, Michael; Guo, Yan; Xuan, Yang; Musa, Taha Hussein; Luo, Pengfei
Abstract : The recent sporadic infections of humans in China with previously unrecognized avian influenza A virus of the H7N9 subtype (A(H7N9)) have caused concern. The aim is to find out the epidemiological and molecular analysis of the PB1-F2 proteins in H7N9 influenza viruses, in Jiangsu province. Sequences were obtained from GISAID database. Data were analyzed by using Molecular Evolutionary Genetics Analysis software and Bayesian Markov chain Monte Carlo method. From March 1, 2013, to May 31, 2014, 53 patients were confirmed to be infected with the H7N9 virus; one was a retrospective case in Jiangsu province. 38 sequences of PB1 in H7N9 of Jiangsu were obtained from the GISAID online and were then divided into three lineages. Of these sequences, 4 sequences and 3 sequences encode an N-terminally truncated PB1-F2 (52aa)polypeptide and C-terminally truncated PB1-F2 (76aa) polypeptide, respectively. The remaining sequences encode a full-length PB1-F2 (90aa). We estimated a mean evolutionary rate of 3.053 × 10 −3  subs/site/year (95% HPD: 2.021 × 10 −3 –4.051 × 10 −3 ). The site-by-site analysis of selection pressure analysis revealed positively and negatively (12, 3), respectively, selected sites. Influenza A (H7N9) virus adapting into new host, PB1-F2 of H7N9, might be faced with higher selection pressures.